2003
DOI: 10.3171/jns.2003.98.2.0371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human amniotic fluid on peripheral nerve scarring and regeneration in rats

Abstract: Preliminary data show that HAF enhances peripheral nerve regeneration. The preventive effect of HAF on epineural scarring and the rich content of neurotrophic and neurite-promoting factors possibly contribute to this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 38 publications
0
46
0
2
Order By: Relevance
“…50 It is interesting that a fetal incision made early in gestation will heal without a scar whereas one made in late gestation heals with scar formation. Two theories predominate: the first is that hyaluronic acid, which is found in high levels in AF, inhibits collagen synthesis.…”
Section: Other Interesting Aspects Of Afmentioning
confidence: 99%
“…50 It is interesting that a fetal incision made early in gestation will heal without a scar whereas one made in late gestation heals with scar formation. Two theories predominate: the first is that hyaluronic acid, which is found in high levels in AF, inhibits collagen synthesis.…”
Section: Other Interesting Aspects Of Afmentioning
confidence: 99%
“…Human amniotic fluid, which contains high concentrations of HA, was found to enhance peripheral nerve regeneration and to have a preventive effect on epineural scarring when applied to the repair site in rats. 22 Moreover, when treated with HA, similar benefits to healing were observed in the rat model and better conduction velocities and faster recovery were observed in addition to a significant reduction in scar thickness. 2,21 The reduced scar for- Figure 3.…”
Section: Hyaloglidementioning
confidence: 58%
“…Electrophysiological and histopathological results were consistent and parallel in both groups. The results were summarized in Table III. dISCuSSIon Peripheral nerve trauma, with an estimated incidence of 1/1000 in population per year, remains a major cause of morbidity and social disruption (4 (2,6,7,8,23,24,25,26,37). To the best of our knowledge no study has been reported on preventing intraneural scarring by radiation.…”
Section: Latency Measurementsmentioning
confidence: 93%